Minat Beli sebagai Mediasi Pengaruh Brand Image dan Sikap Konsumen terhadap Keputusan Pembelian Batik di Pekalongan (Management Analysis Journal, 2015)
The purpose of this research is to know the influence of brand image and consumer attitudes towards purchase decision of batik directly and indirectly that mediated attract purchase intention of consumer Setono Wholesale Market and International Batik Center. The population in this research is the Consumer of batik at Setono Wholesale Market and International Batik Center (IBC) Pekalongan. The number of samples that are used in this research is 116 people by using accidental sampling with non probability sampling approach. Method of data collection using the questionnaire. Data analysis using regression analysis and path analysis. This research concluded that brand image has positive and significant effect directly on purchase decision, but consumer attitudes not significant effect directly on purchase decision. Whereas the brand image and consumer attitudes has positive and significant impact indirectly on purchase decision through purchase intention of consumer Setono Wholesale Market and International Batik Center. The conclusions of this study is proved that purchase intention can be mediated effect of brand image and consumer attitude on purchase decision